Numerical analysis of the ducted ventilation and jet fans systems in an enclosed car park - Tneh, Xuan (2023)
In recent years, the ductless impulse jet fans ventilation system has been increasingly preferred over the traditional ducted ventilation system for car park ventilation applications. Aside from ventilation, the jet fans system offers several additional advantages such as low design complexity, cost-saving, space-saving, and low maintenance which make it to supersede the ducted system. Despite all the advantages, ventilation performance remains the primary concern for every car park ventilation system. The complex geometry of car parks can contribute to a highly unpredictable airflow behaviour when jet fans are used. Therefore, an experimental approach like CFD modelling is required for an accurate evaluation of the ventilation performance. In this project, an impulse jet fans system was designed in strict accordance with the authorities’ requirements for the existing block KB basement car park at UTAR Sungai Long campus. A detailed CFD modelling was carried out to compare the ventilation performance between the existing ducted ventilation system and the jet fans system in the enclosed car park during a fire. The results have shown that the ducted ventilation system can provide a better ventilation during a fire. Although the jet fans system is not as efficient as the ducted model, it managed to fulfil most of the ventilation criteria required by the local authorities.